2004
DOI: 10.1196/annals.1322.038
|View full text |Cite
|
Sign up to set email alerts
|

Virokines in the Pathogenesis of Cancer: Focus on Human Herpesvirus 8

Abstract: During evolution, DNA viruses have captured a broad array of cellular genes involved in immune recognition and growth control that are nonessential for viral replication. The encoded virokines and viroceptors may act as mimetics or antagonists of their cellular homologues, altering signal transduction and cell communication towards survival of virus-infected cells. Human herpesvirus type 8 (HHV8) is the most recently identified human oncogenic herpesvirus. It is associated with Kaposi's sarcoma and lymphoproli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…While there is good evidence from clinical trials summarized in systematic reviews and meta-analyses that interventions aiming at increasing physical activity and/or improving dietary habits are effective [4][5][6][7], only a limited number of studies have investigated clinical long-term effects of interventions which included an additional component focusing on stress management or relaxation. Adding such a component could be considered reasonable for two reasons [8]. First, the reduction of stress or better coping with stressful situations can exert direct protective effects, such as lowering of blood pressure, hormonal changes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…While there is good evidence from clinical trials summarized in systematic reviews and meta-analyses that interventions aiming at increasing physical activity and/or improving dietary habits are effective [4][5][6][7], only a limited number of studies have investigated clinical long-term effects of interventions which included an additional component focusing on stress management or relaxation. Adding such a component could be considered reasonable for two reasons [8]. First, the reduction of stress or better coping with stressful situations can exert direct protective effects, such as lowering of blood pressure, hormonal changes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the convergence between early and recent studies on coping patterns and the characteristics of remarkable survivors justify continued investigation. When we also consider the large body of evidence on mind-body connections in other diseases such as heart disease and human immunodeficiency virus infection [9,13,77], the mind-cancer survival question must be seen as a legitimate and important area worthy of further exploration. However, researchers interested in studying the mind-cancer survival question must be willing to utilize new methods if they wish to generate new knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…The interviews thus showed that the process of return can stir up both positive and negative emotions; emotions that, according to mind/body medicine [8] and the theories on emotions and health, may influence both physical and mental health [56–61,86,97]. Return migrants’ health is an under-researched issue, determined by a ‘cumulative exposure’ to risks and behaviour during the entire migration process; that is, by conditions and events before, during and after the actual migration [98].…”
Section: Resultsmentioning
confidence: 99%
“…For some, it entailed high psychological costs. The experience of negative emotions such as sadness, suffering and worry, which the interviewees expressed, can have negative effects on health, according to the literature [56–61,86,97]. Rosa, who at the time of the interview was working outside León while her children stayed with her mother about half-a-day’s trip from Rosa’s workplace, expressed how during the many years of migrant work she had suffered because of the separation from her children.…”
Section: Resultsmentioning
confidence: 99%